(untitled) (Islas, 2024)
Introduction: The study proposes José Martí’s participation in an ancient creative poetics where the boundaries of the arts interrelate in pursuit of originality and transcendence. Methods: Diachronic study of thinkers who analyze the limits and relationships between the art of painting and literature, to reach a theoretical proposal from the Martí context of the late 19.th century. Results: Theory of the interrelation between painting and literature in the context of José Martí based on three characteristics: interpretation, evocation, and combination. Conclusions: José Martí’s writing style presents an appreciable plastic component, thanks to his knowledge of painting and ancient poets who achieved careful use of the word.